Measurement Invariance of the Brief Resilient Coping Scale (BRCS) in Peruvian and Spanish older adults - Tomás, José M. (2021)
ABSTRACT Although the Brief Resilient Coping Scale (BRCS) has been validated in some European and American countries, there are no studies that evaluate its factorial invariance among different nations. In this sense, the objective of the study is to evaluate the factorial invariance of the BRCS in samples of older adults in Peru and Spain, using multigroup Confirmatory Factor Analysis. 236 older adults from Peru participated (Mean age = 72.8, SD = 6.90) and 133 older adults from Spain (Mean age = 71, SD = 7). In the Peruvian sample 78.4% were women and 21.6% men; while in the Spanish sample the majority were women (69.9%). The BRCS was scalar invariant but not strictly invariant between Spain and Peru. Our results found invariance of the structure, factor loadings and intercepts in both countries. These results support the use of BRCS in studies that compare the resilience between samples of older adults in both countries, and encourage applied research for the development of resilience in older adults in Spain and Peru.